Iron Promoted Ring Opening and Ring Closing Cascade (ROCC) Reaction of C3-(2-(phenylethynyl)phenyl)isoxazoles Leading to 3-Imino-1,3-diphenylpropenols and Isoindolin-1-ylidene Derivatives - Behera, Manoranjan; Gudipati, Ramakrishna; Karri, Raghavulu; Vankudoth, Jayaram; Poosa, Mallesham; Basu, Keloth; Ethiraj, Krishna S (Synthesis)
The study reports the efficient synthesis of different functionalized isoindolin-1-ylidene derivatives through FeCl3/Li2CO3 mediated cleavage of isoxazole. The highlight of the work is the sequential reductive ring-opening of C3-(2-(phenylethynyl)phenyl)ortho-alkynyl-isoxazole and intramolecular 5-exo-dig cyclization of ortho-alkynyl-isoxazole. Additionally, we reported that Fe/NH4Cl could be used to generate 3-imino-1,3-dipheylpropenols from isooxazole. Using this protocol, densely substituted N-heterocyclic compounds can be assembled in simple and efficiently. This is the first report for the synthesis of isoindolin-1-ylidene derivatives using FeCl3/Li2CO3 using isoxazole as starting material